CANADA'S NEW IMMIGRATION ACT: AN AFFRONT TO THE CHARTER AND CANADA'S COLLECTIVE CONSCIENCE? - Drumbl, Mark (Revue de droit de l'Université de Sherbrooke, 1994)
This essay explores the constitutionality of sections 46.01(1) and 19(1)(c.1)(i) of the federal Immigration Act. These sections empower immigration officials to exclude from the refugee determination process any claimant who has arrived in Canada via a "safe" third country or who has been determined to have committed a criminal offence in the home country, unless the claimant falls into several narrow exceptions provided by the statute. The author submits that these provisions violate the procedural requirements of fundamental justice guaranteed by section 7 of the Canadian Charter of Rights and Freedoms. A further investigation is made as to whether these statutory provisions offend the specific rights provided by sections 11(d), 11(g), 12, 14 and 15(1). As well, the essay addresses the question as to whether ss. 46.01(1) and 19(1)(c.1)(i) can constitute reasonable limits under Charter section 1. Ultimately, the author proposes several suggestions as to how these sections can be amended so as to ensure that they attain their policy objectives while respecting both the Charter and the United Nations Convention Relating to the Status of Refugees. As immigration issues are increasingly thrust into the public policy arena, maintaining this balance could become problematic, yet nonetheless important.